Efektivitas Konseling Kelompok Teknik Self Management Untuk Mereduksi Kecanduan Game Online (Pada Siswa Kelas VIII) di SMP Negeri 1 Pundong - Setyowati, Aprilia; Suardiman, Siti Partini; Lestari, Novita Tri (Indonesian Journal of Educational Counseling, 2023)
Research conducted directly in schools showed that several students experienced moderate and high levels of online game addiction. The purpose of this study was to determine the effectiveness of self- management technique group counseling to reduce online game addiction in class VIII students. This research uses pre-experimental quantitative research with one group pretest-posttest research design. The findings in this study were students who experienced the negative impact of online game addiction such as withdrawing and not being able to socialize with the surrounding environment, there were also students who ruled out the primary need to play online games. The instrument in this study used an online game addiction scale that had been tested for validity and reliability with the help of SPSS 25. The paired sample t-test was used in this study as a decision-making process with the help of the SPSS 25 program. The results obtained from the paired sample t-test test with a significant level (α) of 0.05 shows the results of Sig. (2-tailed) < significant level that is equal to 0.006 < 0.05 so that Ha is accepted and H0 is rejected. It can be concluded that self-management technique group counseling is proven to be effective in reducing students who are addicted to online games